Massively parallel sequencing of endometrial lavage specimens for the detection of cancer-associated mutations in atypical and non-atypical endometrial hyperplasia - Weng, Cindy Hsuan; Wu, Kai-Yun; Wang, Chin-Jung; Huang, Huei-Jean; Tsai, Chia-Lung; Lin, Chiao-Yun; Ro, Aileen; Lai, Chyong-Huey; Chao, An-Shine; Wu, Ren-Chin; Chao, Angel (Frontiers in Medicine, 2022)
Background Endometrial hyperplasia (EH), particularly with atypia, is considered an antecedent of endometrial adenocarcinoma. In this study, we aimed to apply massively parallel sequencing of endometrial lavage specimens for the detection of cancer-associated mutations in atypical (AEH) and non-atypical endometrial hyperplasia (NEH). The identified alterations were compared with those detected in tissue samples. Materials and methods Endometrial lavage specimens and parallel biopsy samples (n = 11 for AEH and n = 9 for NEH) were obtained from 18 women (9 with AEH and 9 with NEH) who received an office hysteroscopy for suspected endometrial lesions. All samples were tested for somatic mutations in hotspot regions of 72 cancer-associated genes by massively parallel sequencing. Results On analyzing sequencing data, the presence of at least one cancer-associated gene mutation was identified in 72.7% and 44.4% of endometrial lavage specimens obtained from women with AEH and NEH, respectively (p = 0.362, 95% confidence interval = 0.72−3.70). The concordance rates between mutations identified in endometrial lavage specimens and endometrial biopsies were 54.5% and 0% from women with AEH and NEH, respectively (p = 0.014). A patient with NEH harbored mutations in endometrial lavage with the same mutations found in the tissue specimen at low allele frequency below detection cutoff, raising the suspicion of missed focal atypia. Conclusions EH is characterized by a high burden of cancer-associated mutations, particularly in the presence of atypia. Our study, albeit performed with a relatively small number of samples, indicates that their detection by massively parallel sequencing of endometrial lavage is feasible. Our findings may allow tailoring of endometrial biopsies to the individual risk of AEH; additionally, they can pave the way towards less invasive surveillance protocols in patients with known EH.